The H.264 advanced video compression standard - Richardson, Iain E. G. (Wiley, 2010)
H.264 Advanced Video Coding or MPEG-4 Part 10 is fundamental to a growing range of markets such as high definition broadcasting, internet video sharing, mobile video and digital surveillance. This second edition of the H.264 Advanced Video Compression Standard reflects the growing importance and implementation of H. 264 video technology. Offering a detailed overview of the system, it explains the syntax, tools and features of H.264 and equips readers with practical advice on how to get the most out of the standard.